126 Does hypertrophic cardiomyopathy genotype affect tissue doppler imaging parameters over 3-year follow-up period?. (5th June 2017) - Ding, Wern Yew; Meah, Mohammed; Cooper, Robert; Oxborough, David; Somauroo, John
Abstract : Introduction: Recent studies suggest that tissue Doppler imaging (TDI) have prognostic value in hypertrophic cardiomyopathy (HCM). We aimed to identify if there was a difference in rate of deterioration of TDI values of diastolic function and longitudinal systolic function according to genotype status. Methods: Aprospective, single-centre observational study over 33 months was undertaken. Twenty-six HCM patients were assigned a group according to genotype status (G+ve (n=14) vs G-ve (n=12)). Differences in baseline and follow-up TDI parameters were compared using an independent samples t-test. Results: The mean follow-up was 32.8±2.5 months. A standard 16-gene panel was performed in all patients. Fourteen patients (54%) were G+ve (4 MYBPC3, 3 M7H7 and 7 others). G+ve patients were more likely to be male (57%), younger (39 vs 66 years, p=0.0003) and have a family history of HCM (43 vs 8%, p=0.048). There was no difference in baseline diastolic septal diameter (G+ve 16.1±5.3 mm vs G-ve 17.4±7.3 mm, p=0.6) or ejection fraction (G+ve 64±2% vs G-ve 63±2%, p=0.697). TDI parameters during follow up revealed the magnitude of deterioration in medial E, medial E/E, lateral E and lateral E/E was greater in G-ve compared to G+ve patients. There was also a trend for a greater decrease in medial and lateral S in G-ve patients. During follow up we did not observe any significant differences in the change of LA diameter (G+ve+3.29(±6.29) vs G-ve+3.08(±5.50), p=0.932) or LV max wall thickness (G?+ve −1.07±5.05 vs G-ve+0.20±2.61, p=0.440). Overall changes in sudden cardiac death (SCD) risk scores remained similar (G+ve+0.27(±0.48) vs G-ve+0.75(±0.64), p=0.378). There were no sudden cardiac deaths or shockable events. Conclusion: In this single-centre HCM clinic, despite no change in SCD risk scores or measurements of cardiac morphology, G-ve patients have a greater rate of deterioration of TDI parameters with a significant reduction in diastolic filling and a trend towards reduction in longitudinal systolic function. Although G-ve patients were older than G+ve, the rate of decline in TDI velocities over a 33 month period is greater than what would be expected in the normal ageing population.